Alexithymia, Fear of Intimacy, and Relationship Satisfaction. (April 2022) - Lyvers, Michael; Pickett, Louisa; Needham, Katarina; Thorberg, Fred Arne
Alexithymia, fear of intimacy, attachment security, and mood variables were examined as predictors of satisfaction in couple relationships after accounting for age, sex, relationship length, and marital status. Participants were 158 adults (52% women and 48% men) in an ongoing couple relationship for 1-19 years. They completed validated measures of the variables of interest online. Bivariate correlations were significant for all predicted associations. Multiple mediation modelling examined the hypothesis that the low relationship satisfaction reported by those with alexithymia can be explained by fear of intimacy, insecure attachment, and negative affect, after accounting for relevant covariates. Mediation was indicated for fear of intimacy and negative affect. Such factors may merit particular attention by clinicians working with alexithymic clients in couples therapy.